2009
DOI: 10.1007/s10453-009-9148-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of environmental factors and their effects on fungal spores in the atmosphere of a tropical urban area (San Juan, Puerto Rico)

Abstract: In Puerto Rico, respiratory diseases affect a significant percentage of the population, and it is possible that the environmental factors unique to the island, such as easterly winds, dense vegetation, and high humidity, may increase the concentration of airborne biological particulates that could distress susceptible individuals. As most studies characterized fungal spores and pollen in temperate zones, we wanted to describe their concentrations in a tropical zone. The Allergenco Ò (MK3) spore trap was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
78
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 33 publications
14
78
1
8
Order By: Relevance
“…When the wind speed is less than 5m/s, the fungal spore's concentration decreased, but when the wind velocity is more than 5m/s the concentration of fungal spores increased (Lin & Li, 2000). On the other hand, wind can act as a dispersal and diluting factor for spores when the wind is high and so decrease the concentration of spores significantly (Quintero et al, 2010). Fluctuations in the wind velocity are significantly associated with changes in spore's concentration and particularly when other meteorological factors are optimum (Sakiyan &Inceoglu, 2003).…”
Section: Meteorological Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…When the wind speed is less than 5m/s, the fungal spore's concentration decreased, but when the wind velocity is more than 5m/s the concentration of fungal spores increased (Lin & Li, 2000). On the other hand, wind can act as a dispersal and diluting factor for spores when the wind is high and so decrease the concentration of spores significantly (Quintero et al, 2010). Fluctuations in the wind velocity are significantly associated with changes in spore's concentration and particularly when other meteorological factors are optimum (Sakiyan &Inceoglu, 2003).…”
Section: Meteorological Parametersmentioning
confidence: 99%
“…The most significant meteorological factor which positively correlated to fungal airspora is the temperature. A positive correlation was found between temperature and airborne fungal spores (Aydogdu & Asan, 2008), including certain fungal genera Aspergillus (Adhikari et al, 2006), Cladosporium (Quintero et al, 2010) and Alternaria (Reyes et al, 2009). Grinn-Gofroń & Bosiacka, (2015) demonstrated that and through a 4-years study, Alternaria, Drechslera type and Cladosporium spores were displayed their maximum abundance at higher mean temperature values.…”
Section: Meteorological Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…When visibility reaches near-zero serious traffic accidents have cost lives and cause traffic collapsing when high ways cut out of service for extended periods of time [23]. Beside fine particles, spores and contaminants associated with dust and aerosol can adversely impact human health, causing a range of issues from respiratory infections to toxic exposure [24,25]. Understanding the complex issue of air pollutants and quantifying the contribution of different meteorological parameters, in parallel with the given widespread concern of ambient air pollution in developing countries and its broad ranging impacts, the present study is focused on investigation of air pollution occurring at one of the densest industrial areas located in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%